Internal and external contexts influencing future accountants: The lens of experienced auditors - Ilias, Azleen; K Ghani, Erlane; Mohammad, Kamaruzzaman; Mohd Ali , Mazurina; Atikah Rosley, Nor (Edelweiss Applied Science and Technology, 2024)
This study examines the factors influencing future accountants from the lens of experienced auditors. This study employs a qualitative case study design, focusing on the challenges and issues faced by future accountants, with the aim of enhancing career opportunities that align with employer needs. Interviews with eight experienced auditors, along with the analysis of public documents from the respective accounting regulatory authority and the Ministry of Higher Education, provided the data for this case study. Based on the insights of the experienced auditors, this study developed two contexts, namely an internal and an external context, which could benefit employers and future accountants. The internal context includes attitude and behaviour, continuous learning and adaptability, technical skills, technical knowledge, and career development. The external context includes university standards, the needed IT skills, lack of soft skills, and inability to acquire technical knowledge. The specific factors for both the internal and external contexts could be employer expectations, university requirements, and graduate interest in this area of accounting, which tailor the HalaTuju 4 and MIA competency frameworks. The findings of this study provide new insights in accounting education that can contribute to future research. Furthermore, this study can provide insights into skills, knowledge, and potential factors that are important for future accounting professionals, which could also be included in the university curriculum to accommodate Hala Tuju 4.